"I Guess I Didn't Like That Word Unfortunately": Standardized Patients' Unscripted Techniques for Training Medical Students. Issue 5 (October 2021) - Koski, Kaisu; Ostherr, Kirsten
Abstract : Introduction: This article explores tacit techniques embedded in standardized patients' (SPs) unscripted dialog in a context of breaking bad news (BBN) education. It identifies a technique in which the SP explicitly repeats 1 or more of the medical student's words and analyzes the function and impact of this technique. Methods: This film-based ethnographic inquiry used conversation analysis to examine so-called echo utterances, through which the SP repeats all or part of what the student has said. The data set includes 9 student encounters with 2 female SPs who specialize in the BBN simulation. Results: The authors identified a technique of "repair request" used by the SPs to provide an opportunity for the student to reformulate their utterance in character. Repair requests emerged from 4 main types of student speech: speculative language, inappropriate utterances, awkward timing, and medical jargon. Conclusions: The technique of repair request is used to heighten the student's language sensitivity and foster the ability to respond to criticism or misunderstanding in character. Discovery of the tacit, unscripted technique of repair request in this study provides an opportunity to disseminate this technique in SP training for BBN and other simulation scenarios. These findings suggest the need for further research to identify additional tacit techniques used by SPs to improve medical education.